Biologically Active Vitamin B12 Compounds in Foods for Preventing Deficiency among Vegetarians and Elderly Subjects - Watanabe, Fumio; Yabuta, Yukinori; Tanioka, Yuri; Bito, Tomohiro (Journal of agricultural and food chemistry, 2013)
The usual dietary sources of vitamin B12 are animal-source based foods, including meat, milk, eggs, fish, and shellfish, although a few plant-based foods such as certain types of dried lavers (nori) and mushrooms contain substantial and considerable amounts of vitamin B12, respectively. Unexpectedly, detailed characterization of vitamin B12 compounds in foods reveals the presence of various corrinoids that are inactive in humans. The majority of edible blue-green algae (cyanobacteria) and certain edible shellfish predominately contain an inactive corrinoid known as pseudovitamin B12. Various factors affect the bioactivity of vitamin B12 in foods. For example, vitamin B12 is partially degraded and loses its biological activity during cooking and storage of foods. The intrinsic factor-mediated gastrointestinal absorption system in humans has evolved to selectively absorb active vitamin B12 from naturally occurring vitamin B12 compounds, including its degradation products and inactive corrinoids that are present in daily meal foods. The objective of this review is to present up-to-date information on various factors that can affect the bioactivity of vitamin B12 in foods. To prevent vitamin B12 deficiency in high-risk populations such as vegetarians and elderly subjects, it is necessary to identify plant-source foods that contain high levels of bioactive vitamin B12 and, in conjunction, to prepare the use of crystalline vitamin B12-fortified foods.